PROGRAM TWENTY DAYS WITH YOUR BOOK DALAM MENINGKATKAN DAYA BACA MAHASISWA STUDI DESKRIPTIF PROGRAM UNIT KERJA MAHASISWA UNP - Musliani, Musliani; Primadesi, Yona (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2024)
This research aims to describe how the Twenty Days with Your Book   program works and to describe its benefits in increasing the reading ability of members at UKM PPIPM UNP. This type of research is qualitative research with descriptive methods. Interviews, observation and documentation were research instruments used to collect data involving seven informants consisting of the person in charge of the program and participants who took part in the Twenty Days with Your Book   program. The data analysis techniques used are data collection, data reduction, and drawing conclusions. The results of this research show that the implementation of the Twenty Days with Your Book   program has been carried out in accordance with planning starting from the program concept which has been designed and implemented well, the program targets are right on target, the program implementation indicators have been achieved because they exceed 60% of their targets, the realization procedures have been carried out well. , the selection of reading materials is appropriate but needs improvement, and the evaluation process is carried out well. The benefits they felt based on changes in behavior after participating in the program showed positive changes that were visible in the way they set goals for reading, the process of selecting reading materials, increased reading comprehension, and more efficient use of time. Then the benefits they felt related to their reading ability showed a visible development in the way they drew conclusions after reading, the way they found the main points of the paragraphs and the participants' increased understanding of the reading.